Interactions Between Neural Progenitor Cells and Microglia in the Subventricular Zone: Physiological Implications in the Neurogenic Niche and After Implantation in the Injured Brain - Matarredona, Esperanza R.; Talaverón, Rocío; Pastor, Angel M. (Frontiers in Cellular Neuroscience, 2018)
The adult subventricular zone (SVZ) of the mammalian brain contains neural progenitor cells that continously produce neuroblasts throughout life. These neuroblasts migrate towards the olfactory bulb where they differentiate into local interneurons. The neurogenic niche of the SVZ includes, in addition to neural progenitor cells and neuroblasts, astrocytes, ependymal cells, blood vessels and the molecules released by these cell types. In the last few years, microglial cells have also been included as a key component of the SVZ neurogenic niche. Microglia in the SVZ display unique phenotypic features, and are more densely populated and activated than in non-neurogenic regions. In this article we will review literature reporting microglia-neural progenitor cell interactions in the SVZ and the role of this bilateral communication in microglial function and in neural progenitor cell biology. This interaction can take place through the release of soluble factors, extracellular vesicles or gap junctional communication. In addition, as neural progenitor cells are used for cell replacement therapies, they can establish therapeutically relevant crosstalks with host microglia which will also be summarized throughout the article.